Interpretation of mushroom as a common therapeutic agent for Alzheimer's disease and cardiovascular diseases. (1st November 2016) - Rahman, Mohammad Azizur; Abdullah, Noorlidah; Aminudin, Norhaniza
Abstract: Alzheimer's disease (AD) and cardiovascular diseases (CVD) share common etiology and preventive strategies. As the population of old-aged people is increasing worldwide, AD complications tend to afflict global healthcare budget and economy heavily. CVD is the prime cause of global mortality and remains a grave threat to both the developed and the developing nations. Mushroom bio-components may be promising in controlling both diseases. Based mainly on in vitro, ex vivo, cell line and animal studies, this review interprets the polypharmaceutic role of mushrooms treating AD and CVD.